Between dispersion and volatility - Millán, José-Antonio (Anuario ThinkEPI, 2012)
The problem of dispersion of the conversations on social networking sites (Facebook, Google+, Twitter, etc.) is presented. The threads of people´s conversation who have contributed with their own comments to your post are not always next to it. Despite the existence of partial solutions, a tendency to limit the discussion and the discovery only to our contacts is identified.
Keywords: Social media; Social net sites; Twitter; Facebook; Google; Weblogs; Blogs; Dispersion of the conversation; Comments gathering.